Implementation of Gamification in Al-Quran Learning at Madrasah Diniyah al-Iman Kotabumi - Umar Najih Zein; Syahrudin Syahrudin (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study explores the implementation of gamification in Al-Quran learning at Madrasah Diniyah al-Amiin Kotabumi as an effort to enhance students' engagement, motivation, and learning outcomes. The research aims to analyze how gamification elements such as points, badges, leaderboards, and interactive challenges are integrated into the learning process, as well as their impact on students’ interest and memorization skills. A qualitative descriptive method was employed through observation, interviews with teachers and students, and documentation review. The findings reveal that gamification strategies successfully increase student participation and create a more enjoyable learning atmosphere, which in turn improves students’ ability to memorize and understand the Qur’an. However, the study also identifies several challenges, including limited teacher training in digital tools and the need for adequate facilities. Overall, gamification proves to be an effective approach for optimizing Al-Quran learning in a traditional madrasah setting when supported by proper planning and resources.